2022
DOI: 10.3389/fgene.2022.845305
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Artificial Intelligence in Prevention and Treatment of COVID-19 Pandemic

Abstract: The unprecedented outbreak of the Corona Virus Disease 2019 (COVID-19) pandemic has seriously affected numerous countries in the world from various aspects such as education, economy, social security, public health, etc. Most governments have made great efforts to control the spread of COVID-19, e.g., locking down hard-hit cities and advocating masks for the population. However, some countries and regions have relatively poor medical conditions in terms of insufficient medical equipment, hospital capacity over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Telehealth has also proven beneficial for inpatient care, specifically to help balance clinical service provision with surging demand across physical or geographic boundaries, conserving personal protective equipment, and providing remote patients connections to family and friends (20,21). Telehealth has several key strengths that can improve emergency response services when the environment is in a biological hazard and during infectious disease outbreaks (22). This research showed that there was no relationship between age and occupation factors on PNC telehealth readiness; meanwhile, there was a significant relationship between education and income with readiness in PNC telehealth.…”
Section: Discussionmentioning
confidence: 78%
“…Telehealth has also proven beneficial for inpatient care, specifically to help balance clinical service provision with surging demand across physical or geographic boundaries, conserving personal protective equipment, and providing remote patients connections to family and friends (20,21). Telehealth has several key strengths that can improve emergency response services when the environment is in a biological hazard and during infectious disease outbreaks (22). This research showed that there was no relationship between age and occupation factors on PNC telehealth readiness; meanwhile, there was a significant relationship between education and income with readiness in PNC telehealth.…”
Section: Discussionmentioning
confidence: 78%
“… 32 Statistical models can rely on statistical regression models such as the Gaussian model, where the dynamics of the epidemic outbreaks are identified with time series of the identified infected cases. State space models, also referred to as traditional mathematical models, 33 describe the dynamics of the epidemic using differential equations by subdividing the population into several categories. These models include the susceptible-infected (SI) model, SIS model, susceptible-infected-recovered (SIR) model, the susceptible-exposed-infected-recovered (SEIR) model, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Machine learning methods can include different types of models such as linear regression models, polynomial regression models, support vector machine learning, artificial neural network (ANN) models, etc. 33 …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, before the governments realized and initiated the containment measures, COVID-19 spread to various countries where people did not have self-protection awareness measures such as wearing masks, social distancing, etc. Countries with a limited healthcare infrastructure suffered more due to a lack of vaccines, systematic treatment, and elevated hospital bills that were not affordable [ 9 ]. Still, there is no effective antiviral drug; patients are treated with general treatment methods such as bed rest, ventilators, and conventional antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Artificial Intelligence (AI) has received more attention due to its ability to observe, make decisions about, and interpret a huge volume of data in different fields [ 9 ], which include computer science, healthcare, drug discovery, engineering, infectious diseases, and government management, especially in this pandemic. Modern medicine and improvements in the healthcare sector have brought a huge amount of patient data related to medications.…”
Section: Introductionmentioning
confidence: 99%